(untitled) (Journal of Advanced Veterinary and Animal Research, 2020)
COVID-19 is now a pandemic. Like other countries, Bangladesh is putting all its efforts to combat this pandemic. Dengue is a mosquito-borne viral infection causing a severe flu-like illness and, sometimes causing a potentially lethal complication called severe dengue. At this very crisis moment, there are reports on new cases of dengue in Bangladesh. More efforts now need to be taken for the control of dengue along with COVID-19 control measures. Adv. Vet. Anim. Res., 7(2): 218-219, June 2020